College Algebra (11th Edition)

Published by Pearson
ISBN 10: 0321671791
ISBN 13: 978-0-32167-179-0

Chapter R - Section R.4 - Factoring Polynomials - R.4 Exercises - Page 40: 86



Work Step by Step

Let $z=(2y-1).$ Then the given expression, $ (2y-1)^2-4(2y-1)+4 ,$ is equivalent to \begin{array}{l}\require{cancel} z^2-4z+4 .\end{array} The two numbers whose product is $ac= 1(4)=4 $ and whose sum is $b= -4 $ are $\{ -2,-2 \}$. Using these two numbers to decompose the middle term of the expression, $ z^2-4z+4 ,$ then \begin{array}{l}\require{cancel} z^2-2z-2z+4 \\\\= (z^2-2z)-(2z-4) \\\\= z(z-2)-2(z-2) \\\\= (z-2)(z-2) \\\\= (z-2)^2 .\end{array} Since $z=(2y-1)$, then the expression $ (z-2)^2 $ is equivalent to \begin{array}{l}\require{cancel} (2y-1-2)^2 \\\\= (2y-3)^2 .\end{array}
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.